Extrusion of poly(vinylidene fluoride) recycled filaments : effect of the processing cycles on the degree of crystallinity and electroactive phase content - Silva, Marco Aurélio Pinto (2013)
This study analyses the possibility of reprocessing used poly(vinylidene fluoride), PVDF, maintaining the main properties critical for its use in piezoelectric sensor/actuator applications. The influence of multiple reprocessing cycles of PVDF on crystallinity and ß-phase content fundamental for its electroactive behaviour, was studied. Nine reprocessing cycles were completed and it was found that the material preserved the characteristics required for its use as piezoelectric polymer without significant degradation.